Hyperferritinaemia and hyperuricaemia — a causal connection?. Issue 11 (November 2018) - Richette, Pascal; Latourte, Augustin
A variety of comorbidities of gout exist, but most of these associations are not causally linked. Mendelian randomization analysis of genome-wide association study data now suggests that iron overload might increase serum uric acid levels and hence the risk of gout flares.